2013
DOI: 10.1039/c3dt00037k
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic calcium and strontium borohydrides as initiators for the polymerization of ε-caprolactone and l-lactide: combined experimental and computational investigations

Abstract: [Ca(BH4)2(THF)2] (1a), a known compound, was easily prepared following a convenient new procedure from [Ca(OMe)2] and BH3·THF in THF. Reaction of 1a with KCp* (Cp* = (η(5)-C5Me5)) and K{(Me3SiNPPh2)2CH} in a 1 : 1 ratio in THF resulted in the corresponding dimeric heteroleptic mono-borohydride derivatives [Cp*Ca(BH4)(THF)n]2 (2a) and [{(Me3SiNPPh2)2CH}Ca(BH4)(THF)2] (3a), respectively. Both compounds were fully characterized and the solid-state structure of 3a was established by single crystal X-ray diffractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 74 publications
1
21
0
Order By: Relevance
“…The calcium complex 7 also showed comparable activity towards the ROP of ε-CL with magnesium analogues (5 and 6) with narrow PDI values and controlled molecular weight distributions (Table 2, entries 7-11). Indeed, the sluggish reactivity of the calcium complexes is very similar to that observed in some previously reported studies using other calcium complexes for ROP of ε-CL, 45,46 we have noted living polymerization characteristics at room temperature without using any initiating agent like alcohol (entry 9, PDI = 1.5 and M w = 50 483) indicating that the triphenylmethyl group on the ligand backbone strongly influences the activity of calcium complexes towards the ROP of ε-CL. We anticipated that strontium (8) and barium (9) complexes could be more active than those of magnesium and calcium complexes having bulky iminopyrrolyls due to the larger ionic radii of Sr 2+ and Ba 2+ ions.…”
Section: Rop Studies On ε-Clsupporting
confidence: 86%
“…The calcium complex 7 also showed comparable activity towards the ROP of ε-CL with magnesium analogues (5 and 6) with narrow PDI values and controlled molecular weight distributions (Table 2, entries 7-11). Indeed, the sluggish reactivity of the calcium complexes is very similar to that observed in some previously reported studies using other calcium complexes for ROP of ε-CL, 45,46 we have noted living polymerization characteristics at room temperature without using any initiating agent like alcohol (entry 9, PDI = 1.5 and M w = 50 483) indicating that the triphenylmethyl group on the ligand backbone strongly influences the activity of calcium complexes towards the ROP of ε-CL. We anticipated that strontium (8) and barium (9) complexes could be more active than those of magnesium and calcium complexes having bulky iminopyrrolyls due to the larger ionic radii of Sr 2+ and Ba 2+ ions.…”
Section: Rop Studies On ε-Clsupporting
confidence: 86%
“…Under these conditions, all complexes successfully ring-open polymerized CL at room temperature in toluene ( Table 2). (14), B2-Yb-O1 87.59 (14), B2-Yb-S 164.57 (14), C1-Yb-N 65.84(9), C1-Yb-O1 84.99(9), C1-Yb-P1 32.11 (7), C1-Yb-P2 35.31 (7), C1-Yb-S 67.90 (7), N-Yb-O1 150.84 (10), N-Yb-S 87.21 (7), O1-Yb-S 81.77 (7), P1-C1-P2 121.8 (2). Running the polymerization in a more diluted reaction medium remained successful (Table 2, entries 9, 10).…”
Section: Resultsmentioning
confidence: 99%
“…Calculation studies revealed that the negative charge is mainly localized on the carbene carbon atom of the ligand backbone and that the charge delocalization from carbon to nitrogen is less important. 6,14,16,20,[36][37][38][39][40][41][42][43][44][45][46][47][48][49] In this context, some very efficient rare-earth metal initiators ligated by {CH(PPh 2 NSiMe 3 ) 2 } − have been unveiled for polymerization reactions. Mostly six membered metallacycles (N-P-C-P-N-M) are formed by chelation of the two imine groups to the metal center, adopting a pseudo-boat conformation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the moderate reactivity of the strontium complexes is very similar to that observed in previously reported studies using other strontium complexes for ROP of 3-caprolactone. 29 Since the larger ion radius barium complexes have been reported to be more active than the calcium and strontium congeners in ROP, 30,31 we tested compound 6a or 6b as a catalyst and observed an enhanced rate of polymerisation (Table 1, entries 6-10). In the case of strontium, higher reactivity was observed for conversion of 3-caprolactone to poly-caprolactone and up to 500 3-CL units were successfully converted in high yields (75-90 per cent), within 15 and 10 minutes respectively, at 25 C. The control over the ROP process was rather good, affording PCLs, featuring a considerable match between the observed (as determined by GPC) and calculated molar mass values, as well as moderate dispersity data (PDI ¼ M w /M n < 1.94).…”
Section: Ring-opening Polymerisation Studymentioning
confidence: 99%